TEST OF BACTERIOCIN ANTIMICROBIAL ACTIVITY OF PROBIOTIC BACTERIA ISOLATED FROM TIGER SHRIMP (Penaeus monodon Fabricus) - Anita R Sidabutar; Feliatra '; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Probiotic bacteria is a type of lactic acid bacteria (BAL) that produces compound of bacteriocin antimicrobial. Research to analyzed the bacteriocin of 5 probiotic bacterial from isolates tiger shrimp (Penaeus monodon Fabricus). The bacteriocin product contained in 2 forms, that i.e. without precipitation (extract bacteriocin) and with precipitation (fragment bacteriocin) used ammonium sulfate (NH4)2SO4. Bacteriocin will be tested activity against pathogen bacterial that cause fish disease was is Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas stutzeri. Inhibitory activity test conducted using paper disc diffusion method. Inhibitory activity bacteriocin with precipitation showed inhibition was higher the biggest than without precipitation. Fragment bacteriocin (BC) with precipitation had inhibitory activity or AU (Activity Unit) i.e. 881,71 mm2/ml at UWH9 isolate toward bacteria test A. hydrophila and P. stutzeri. The biggest Inhibitory activity of extract bacteriocin (CR) without precipitation was 365,65mm2/ml at UWH10 isolate toward bacteria test P. stutzeri.Keywords: Bacteriocin, Pathogen bacterial, Precipitation, Inhibitory activity